The Politics of Perception: Political Preference Strongly Associated with Different Perceptions of Islamist and Right-Wing Terrorism Risk - Snook, Daniel W. (Terrorism and political violence, 2024)
Islamist and extreme right-wing (XRW) terrorism represent about equal levels of risk in terms of casualties in the U.S. over the past decade, yet Islamist terrorists receive far more news coverage, have more serious charges filed against them, are considered more deserving of torture and detainment, and receive harsher prison sentences than XRW terrorists. That Islamist and XRW terrorism elicit such different responses raises the question: Do Americans perceive the risk of Islamist and XRW terrorism differently? To investigate, we measured risk perceptions for Islamist and XRW terrorism in a nationally representative sample of 405 U.S. residents. How Americans perceived the risk of terrorism was strongly associated with their political preferences, such that conservatives perceived Islamist terrorism as the greater risk and liberals perceived XRW terrorism as the greater risk. The political orientation of the news media participants consumed was also significantly related to which type of terrorism they perceived to be a greater risk, in the same pattern. Our results indicate that perceived risk for these types of terrorism tends to be polarized along political fault lines, with implications for risk communication regarding terrorism.